THEORETICAL FOUNDATIONS OF USING SOCIO-CULTURAL TECHNOLOGIES IN PROMOTING A HEALTHY LIFESTYLE IN SOCIETY (Scientific journal of the Fergana State University, 2026)
The article analyzes the pressing issues of forming physical culture and promoting a healthy lifestyle among school-aged children in Uzbekistan. At present, the state policy prioritizes the protection of public health, especially that of children and adolescents. The study scientifically examines the development of the “self-preservation culture” within physical education, the significance of exercise forms, methods, and physical loads, as well as the directions for integrating physical culture with a healthy lifestyle (HLS). In addition, the article highlights the importance of cultivating regular physical activity habits among schoolchildren through the decrees and resolutions adopted by the President and the government. It also presents mechanisms for fostering physical culture, ensuring children’s health, and supporting their functional development through the application of modern pedagogical and methodological approaches.